Al-Raqabah bi Shahadah al-Halal al-Maliziyyah wa Dawruha fi Dhaman Jawdah Muntajat al-Halal - Man, Saadan; Zara'i, 'Umar 'Abduh (Jurnal Fiqh, 2011)
Halal issues, especially those relating to halal food and daily consumed products, have become a popular issue nowadays in parallel with the Islamic awakening in the Muslim world. In Malaysia, halal certification and auditing started back in the 1970?s. Since then it has played an important role in ensuring halal food products in the country and lately, Malaysian Halal certification and its logo have become significantly popular at the international level. This article aims to analyse the process of halal certification, monitoring and auditing organized by the Malaysian Department of Islamic Development (JAKIM). It also focuses on the role of halal auditing and monitoring in assuring the quality of halal food produced by food manufacturers in Malaysia. This article finds that halal certification and monitoring run by JAKIM have significantly ensured the quality of halal products even though there are several continuining issues that they still need to address.